The impact of spiritual intelligence on the health of the elderly in Malaysia - Saad, Zarina Mat; Hatta, Zulkarnain A.; Mohamad, Noriah (Blackwell Publishing Asia Pty Ltd, 2010)
In an attempt to study the impact of spiritual intelligence on the health of the elderly, research has been carried out on 378 elderly people in Perlis, Malaysia.The primary objectives of the study were: (i) to identify the levels of spiritual intelligence and general health of the elderly; (ii) to examine the relationships between spiritual intelligence and health of elderly; (iii) to examine the differences in the level of spiritual intelligence and health based on selected demographic factors; and (iv) to predict the most dominant dimension of spiritual intelligence that affects health.Sets of questionnaires were distributed to gather data.The findings showed that the majority of respondents were in good health, and had excellent spiritual intelligence.It also suggested that spiritual intelligence was positively associated with general health. Those who had higher levels of spiritual intelligence tended to have higher levels of health.The ability to conduct daily life with sanctification based on one’s spiritual belief was the most dominant factor of good health.The study suggested that spirituality is related to health and has a positive effect on participants’ overall health.Based on our findings, we recommend that health practitioners introduce the biopsychosocial-spiritual model when assessing the health of the elderly.